MENGENAL AL-MUNASABAH - Fitri Yani; Faizah; Dona Sholehah (MUSHAF JOURNAL: Jurnal Ilmu Al Quran dan Hadis, 2021)
The Qur'an is the word of God which is also a miracle that was revealed to the prophet Muhammad in Arabic, which reached mankind by means of al-tawatur (directly from the Apostle to his people), which was then contained in the manuscripts. The holy book Al-Quran was revealed by Allah as a guide for mankind, especially for those who are pious. Understanding the instructions contained in the Qur'an needs to be supported by related sciences, for example: asbab an-nuzul, munasabah, makki and madani and so on. Among the many discussions of the Qur'anic sciences, one of them is about munasabah. Munasabah discusses the relationship between one letter or verse with another letter or verse, this is part of the Ulum Al-Qur'an. the scholars of the Qur'an include the science of munasabah, namely knowledge of the relationship, the relationship between verses and suras in the Qur'an as part of the Ulumul Qur'an. As part of the linguistics of the Qur'an, munasabah has an important position in an effort to understand the text of the Qur'an integrally. Because the systematic placement, by some people, is considered to be arranged by God, who of course has wisdom behind the arrangement